INDIVIDUALITY OF PROVERBS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The following article deals with information about the diversity of proverbs that reflect the uniqueness of today's people. There are also opinions about the differences between quotations and folk sayings and their uniqueness in every nation. Further, it is undoubtedly true that individuality of every proverb is guaranteed because the fact that each nation has key characteristics in its history.